(re) Storing Yoruba Traditional Ideals Through Folktale - Rabiu Iyanda (The Journal of Studies in Language, Culture and Society)
Culture is an accumulated pattern of values, beliefs, and behaviours which is shared by an identifiable group of people with a common history and verbal system. Folktale is a culturally oriented people’s story possessed by each culture. It serves as rules and regulations of societies learnt consciously or unconsciously by members of the community. This literary aspect of patterns of life is becoming neglected. This paper is an attempt to revisit these didactic acceptable manners of impacting lives. It views folktales as important traditional aspect in communities with special emphasis on the Yoruba community of Western part of Nigeria. The paper answers the question of identity of “Who am I?” To which culture do I belong, its significance, problems and prospect? What are the accepted norms of behavior for me? The present social values and its’ lapses could be determined from tracing the past through folktale, what could be its benefit and problems in the current global village. The paper submits some plausible suggestions towards having a peaceful and cohesive Yoruba society with the service of fables.